ANALISIS KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN METODE DU PONT SYSTEM - Sandy Yolanda & Fadjar Harimurti (Universitas Slamet Riyadi, 2017)
The purpose of this study is to analyze the financial performance of cigarettecompanies listed on the Indonesia Stock Exchange period of 2011-2015 using DuPont System method. This type of research is descriptive. The population of this studyis tobacco companies listed on the Indonesia Stock Exchange which amounted to 4companies. Sources of data using secondary data sourced from the websitewww.idx.co.id. Data collection used documentation method. Data analysis techniqueusing du pont analysis. The results showed that with the analysis du pont PTHandjaya Mandala Sampoerna, Tbk is the healthiest company compared to othercigarette companies with an average NPM of 13,77% > average industry ratio of6,15%, average TATO 2,64 X> 1.60 X, average ROI 36,43% > industry average11,97%.Keywords: ROI, NPM, TATO, Du Pont Analysis